Expression at the cell surface of biologically active fusion and hemagglutinin/neuraminidase proteins of the paramyxovirus simian virus 5 from cloned cDNA. - Paterson, R G (1985)
cDNAs encoding the mRNAs for the fusion protein (F) and the hemagglutinin/neuraminidase protein (HN) of the paramyxovirus simian virus 5 have been inserted into a eukaryotic expression vector under the control of the simian virus 40 late promoter. The F and HN proteins synthesized in recombinant infected cells are indistinguishable in terms of electrophoretic mobility and glycosylation from the proteins synthesized in simian virus 5-infected cells. In addition, the expressed F and HN proteins have been shown to be anchored in the plasma membrane in a biologically active form by indirect live cell immunofluorescence, the F-mediated formation of syncytia, and the ability of HN to cause the hemadsorption of erythrocytes to the infected cell surface.